Hiperrealitas Pengaruh Penggunaan TikTok dalam Membentuk Eksistensi Diri Mahasiswa Universitas Jember - Hilda Lolita Putri; Noorma Mega Astinaningrum; Wanda Aziza (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Currently, the digital era continues to develop both from information technology and social media has become an inseparable part of everyday life. The Tik Tok application has succeeded in attracting millions of users from all walks of life, from children to adults. The opening of this public space is one of the channels for users to express their opinions and viewpoints freely, which stimulates the growth of lifestyles and behaviors that are different from the reality of their users' lives. The research method used in this type of research is qualitative. The technique of determining informants using purposive sampling technique. The results of this study indicate that the use of TikTok has a significant influence on the formation of a student's self-existence in terms of increasing self-confidence and creating a good self-image in social media.